Literacy, socioconstructivism and neuroscience - Bezerra de França , Rayane (Seven Editora, 2023)
This article focuses on the socioconstructivist educational approach that underlies the didactics of many teachers from the most diverse fields of knowledge. However, it will only be detailed here its implications with regard to literacy. The research that follows was based on a theoretical refinement in line with the neuroscientific perspective of how the human being learns to read and write. The result of the readings and inferences consists, widely and often, in the theories of Vygotsky and Piaget continue to be misinterpreted and transmuted to the scope of education, when they discuss precisely issues related to the biological and psychic development of the child, excluding propositions about the methodological natures of the process of reading and writing. DOI: https://doi.org/10.56238/Connexpemultidisdevolpfut-080